Halo—A Universal Fluorescence Reader Based Threat Agent Detection Platform—A Proof of Concept Study Using SARS-CoV-2 Assays - Walish, Joseph; Cox, Jason; Boone, Jeremy; Stone, Jennifer; Henderson, Nathan; Maloney, Molly; Ma, Joe; Maa, Jonathan; On, Nghiem; Petre, Konrad; Goodwin, Bruce G.; Sozhamannan, Shanmuga; et al. (Frontiers in Public Health, 2022)
Polymerase chain reaction (PCR) remains the gold standard in disease diagnostics due to its extreme sensitivity and specificity. However, PCR tests are expensive and complex, require skilled personnel and specialized equipment to conduct the tests, and have long turnaround times. On the other hand, lateral flow antigen tests are rapid, relatively inexpensive, and can be performed by untrained personnel at the point of care or even in the home. However, rapid antigen tests are less sensitive than PCR since they lack target amplification. It has been argued that rapid antigen tests are better indicators of infection in public health decision-making processes. Hence, there is a critical need to increase the sensitivity of these tests and create innovative solutions to achieve that goal. Herein, we report the development of a low-cost diagnostic platform, enabling rapid detection of SARS-CoV-2 under field or at-home conditions. This platform (Halo™) is a small, highly accurate, consumer-friendly diagnostic reader paired with fluorescently labeled lateral flow assays and custom software for collection and reporting of results. The focus of this study is to compare the analytical performance of Halo against comparable tests in simulated nasal matrix and not in clinical samples. Live virus data has demonstrated limit of detection performance of 1.9 TCID50/test in simulated nasal matrix for the delta variant, suggesting that single-assay detection of asymptomatic SARS-CoV-2 infections may be feasible. Performance of the system against all tested SARS CoV-2 virus variants showed comparable sensitivities indicating mutations in SARS-CoV-2 variants do not negatively impact the assay.